Osteochondrodysplasia in a 9-Year-Old Scottish Fold Cat - Turan, Gulcan; Bozkan, Zeynep (VCOT Open, 2019)
Objective The aim of this study was to share clinical and radiological findings of extremely advanced osteochondrodysplasia.A 9-year-old Scottish Fold cat was presented with the complaint of difficulty in urination, defecation, respiration, standing and walking. Physical findings such as kyphosis, hyperflexion of joints and thick tail and, radiological findings including periosteal bone proliferation in distal extremities, ankylosing changes in spine and tail and, calcification of triceps brachii insertion were consistent with the most advanced osteochondrodysplasia ever documented. Antibiotic medications, anti-inflammatory drugs, vitamin C and enema were administered considering difficulty of urination, defecation and respiration. Then, glycosaminoglycans and prednisolone were administered for osteochondrodysplasia and increase in the movement of the cat was observed in a few days.Conclusion By sharing clinical and radiological findings of severe osteochondrodysplasia in advanced age, the importance of informing breeders and owners about uncontrolled breeding of these cats was emphasized.
Keywords: cat; osteochondrodysplasia; folded ear; Scottish Fold